Biodiesel Production from Rubber Seed Oil by Supercritical Methanol Method - Abdul Shokib; Pramita Gumanti; M. Rachimoellah Rachimoellah (IPTEK The Journal for Technology and Science, 2010)
The purpose of this research is to investigate the effect of reaction temperature, reaction time and molar ratio between methanol and oil on the yield of biodiesel product. Rubber seeds with 45.63 wt% oil content and contained 17 wt% Free Fatty Acid was used as the main feedstock. Supercritical treatment with the methanol temperature of around 350oC and pressure of about 43MPa was used as the reaction method. It was found that yield of biodiesel product increased with the increase of reaction temperature until the temperature of about 350oC, reaction time, until the time of 9 min and molar ratio of methanol to oil until the ratio of 42:1. The highest yield of biodiesel produced was achieved under the reaction temperature of 350oC, reaction time of 9 minutes and 42:1 methanol to oil ratio.